A forgotten centre of ceramic production in Southern Levant: Preliminary analytical study of the Early Bronze Age pottery from Tell el-Far'ah North (West Bank). Issue 9 (15th June 2019) - Medeghini, Laura; Sala, Maura; De Vito, Caterina; Mignardi, Silvano
Abstract: The paper presents an archaeometric investigation of ancient ceramics from the archaeological site of Tell el-Far'ah North (West Bank), dated to the south-Levantine Early Bronze I-II (EB I-II, 3300–2700 BC). The application of mineralogical and chemical analyses by optical and scanning electron microscopy yielded the identification of petro-fabrics that allow the reconstruction of the raw material nature used in the manufacture as well as its provenance. The results indicate that the ceramics were produced using calcareous clays with inclusions of sedimentary rock fragments, calcite crystals, iron oxides and quartz. Two basic fabrics have been identified according to the presence or absence of coarse and angular calcite crystals. The optical activity of the matrix and the presence of calcareous inclusions indicate a maximum firing temperature lower than 850 °C and in the range 700–850 °C for those ceramics showing an initial decarbonation process of calcareous inclusions. The nature of the inclusions supports a local supply of raw materials. Moreover, the comparison between the ceramic material of the two subsequent occupational phases at the site allowed achieving important information about the development of the material and technological knowledge reached by its ancient potters, in the transition from the EB I community to the EB II urban centre.